Przyjaźń domaga się rezygnacji. Kilka aspektów relacji między przyjaciółmi poruszonych w Biblii - Nawrot, Janusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
For Aristotle, the bond of a valuable friendship was created for the sake of its own value of giving friendship or the experience it furnishes, and not for the sake of expediency or the sheer joy of sharing friendship. A sustainable friendship basically finds its roots in what a human being is. Hence, it is loving rather than being loved that makes people real friends, ethically perfect. Biblical authors knew that a true friendship was difficult to obtain and that it could easily be lost. Thus, for their readers, to observe their advice means to obtain valuable hints and guidelines and to be protected from disillusionment. These guidelines had been drawn by them from the experience of everyday life, as a result of watching and drawing conclusions from what they saw following different man’s response to different situations. Might they have been victims to unjust action themselves, or had they committed something that made them feel ashamed, but kept that it in their mind as a warning to their prospective readers? Whatever the answer is, they managed to draw conclusions from the experience that, ultimately, could be helpful in making those who would perpetrate something that would hurt or kill a friendship repent.